SIROMPAK SATU RAGAM MANTRA DALAM TRADISI LISAN MINANGKABAU (Sirompak One of Magical Songs in Oral Minangkabaunese Tradition) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The schematic composition of sirompak magic formula consists of forÂ¬mula and theme repetition. All texts are formula in formulaic expression. The longer the duration of live performance, the more new formula produced by tukang dendang sirompak (the singer) in using filler syllables, substitution system, and balancing words which agrees with the saluang rhythm. Tukang dendang uses three techniques in composing the text that is memorizing, remembering, and recreating. The major theme is sijundai that can cause a victim to fall in love to the philter. This theme is supported by minor themes that tend not to be arranged structurally. These themes can be schematized into three groups. The first group is beginning part that is opening which include with yearning, disappointing, painful, hopeless, and intention to revenge. The second group is the main part that is sijundai. The third group is final part of sijundai closing that is sibabau. The relationship between tukang dendang and his audiences is not close. The audience is more passive beÂ¬cause they do not take part in composition process. Tukang dendang tend to compose the text in live performance. The transmission process is done orally. Lately, the magic-formula of sirompak is transformed in formation-cross that is from sacred oral magic-formula (song) to profane oral tradition.